Using Highlighted Journal Strategy in Teaching Analytical Exposition Text - Kurniawati, Dewi; Kurniawan, Tiza Okta (Universitas Islam Negeri Raden Intan Lampung, 2017)
The objective of this research is to know the influence of using Highlighted Journal Strategy towards students’ writing ability in analytical exposition text at the second semester of the eleventh grade of MAN 1 Central Lampung in academic year of 2015/2016. The research methodology was experimental research with three times of meeting, 90 minutes for each meeting. This design used pre-test and post-test to find out students’ writing ability in analytical exposition text before the treatment and after the treatment. The population of this research was the second grade of MAN 1 Central Lampung. There were five classes and consist of 175 students. The writer used cluster random sampling when the writer took classes of five classes. The first class of experimental class is X1 A1 and the second of control class is X1 A3. In collecting the data, the writer used instruments in the form of writing test. After being tried out, the instruments were used for the pre-test and post-test. After giving the post-test, the writer analyzed the data using T-test formula. From the data analysis, it was found that the result of T-test was T-observed (2.8355) with T-critical (1.668). Since T-observed > T-critical, Ha is accepted. It can be concluded that there is a significant influence of using highlighted journal strategy towards students’ writing ability in analytical exposition text at second semester of the eleventh grade of MAN 1 Central Lampung in academic year of 2015/2016.